The combined effects of climate change and river fragmentation on the distribution of Andean Amazon fishes. (12th August 2020) - Herrera‐R, Guido A.; Oberdorff, Thierry; Anderson, Elizabeth P.; Brosse, Sébastien; Carvajal‐Vallejos, Fernando M.; Frederico, Renata G.; Hidalgo, Max; Jézéquel, Céline; Maldonado, Mabel; Maldonado‐Ocampo, Javier A.; Ortega, Hernán; Radinger, Johannes; et al.
Abstract: Upstream range shifts of freshwater fishes have been documented in recent years due to ongoing climate change. River fragmentation by dams, presenting physical barriers, can limit the climatically induced spatial redistribution of fishes. Andean freshwater ecosystems in the Neotropical region are expected to be highly affected by these future disturbances. However, proper evaluations are still missing. Combining species distribution models and functional traits of Andean Amazon fishes, coupled with dam locations and climatic projections (2070s), we (a) evaluated the potential impacts of future climate on species ranges, (b) investigated the combined impact of river fragmentation and climate change and (c) tested the relationships between these impacts and species functional traits. Results show that climate change will induce range contraction for most of the Andean Amazon fish species, particularly those inhabiting highlands. Dams are not predicted to greatly limit future range shifts for most species (i.e., the Barrier effect). However, some of these barriers should prevent upstream shifts for a considerable number of species, reducing future potential diversity in some basins. River fragmentation is predicted to act jointly with climate change in promoting a considerable decrease in the probability of species to persist in the long‐term because of splitting species ranges in smaller fragments (i.e., the Isolation effect). Benthic and fast‐flowing water adapted species with hydrodynamic bodies are significantly associated with severe range contractions from climate change. Abstract : Future climate change and river fragmentation are predicted to threaten Andean Amazon fishes by promoting significant changes in their distribution. Range fragmentation by dams will decrease the probability to persist of most species. Highland species adapted to fast‐flowing conditions will suffer more severely from range contraction due to climate change.